Analisis dan Perancangan Sistem Informasi Perpustakaan Berbasis Web untuk Meningkatkan Efisiensi Peminjaman dan Pengelolaan Buku - Alya Dyah Sari Harahap; Audira Syifa Amalia Rasyid; Dinda Azzahra; Zatin Niqotaini (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
Libraries are a crucial resource for supporting learning activities and providing information to everyone, especially students. However, many libraries still employ manual management systems, resulting in problems such as delays, recording membership, loan transactions, and reporting, as well as difficulties in data retrieval. This research aims to design a web-based library information system that can improve service effectiveness and simplify library data management. The system development method used is the Waterfall approach, using the Unified Modeling Language (UML) approach as a system design tool. UML is used to describe system processes through use case diagrams, activity diagrams, sequence diagrams, and class diagrams. The designed system has several key features, including book data management, member data management, loan and return transactions, and automated report generation. The research results in a web-based library information system designed to facilitate more organized and faster library management processes while minimizing the potential for errors in data processing.